PENGEMBANGAN MEDIA PEMBELAJARAN KOSAKATA BAHASA JEPANG TINGKAT DASAR DENGAN MENGGUNAKAN MEDIA ADOBE FLASH - Elmardiah Khaidir; Sri Wahyu Widiati; Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is about development adobe flash media as supporting material for learning Japanese vocabulary basic level University of Riau. The purpose of this research is to  that adobe flash media as supporting instructional Japanese vocabulary basic level University of Riau was in line expert standart or validator, so that media viable to use. This research us a “research and development” study. The subject of this research are Japanese college students in 2015/2016. In a way give a questionnaire with 10 question. The location of the research is in Riau University.The method of this development and research is use a Sugiyono design. Among others : 1) incorporation data, 2) planning, 3)basic product development, 4) validation (validator), 5) basic step product revition. The incorporation data method used is with distributing necessity questionnaire validation and trials product. The result of the validation of lecture expert is declared valid to use as learning media with an average percentage of 89,28 %, the result of the validation of media expert is declared valid tu use as learning media with an average percentage of 88,46 %, and the result of trial product validation is 88 %. This research concludes that this learning media viable to use.   Key words : Adobe flash media, research and development, kosakata